Development of a 2D Shape E-Module Based on Project-Based Learning with Scratch to Improve Computational Thinking Skills - Setiawan, Kadek Aldi; Suparta, I Nengah; Suharta, I Gusti Putu (International Journal of Education, Management, and Technology, 2025)
This study aims to develop a flat shapes e-module based on project-based learning (PBL) supported by Scratch to enhance computational thinking skills. The research method used is research and development with three development phases: preliminary research, prototyping, and assessment. The research subjects consisted of 30 students from class VII at SMP High Scope in the limited trial, and 32 and 35 students from SMP Negeri 5 Denpasar in field tests 1 and 2, respectively. SMP High Scope was selected for the limited trial because its student characteristics are similar to those of SMP Negeri 5 Denpasar. In addition, SMP High Scope frequently uses Scratch in its informatics lessons, making it more suitable for identifying and addressing issues with the e-module before further testing in a more general environment. The revisions and feedback from the limited trial were then followed by field tests 1 and 2 at SMP Negeri 5 Denpasar to refine the e-module. The e-module characteristics include learning objectives, estimated time, and project-based materials. The integrated support features include Scratch, learning videos, and evaluation exercises. The e-module was assessed using validation sheets, student and teacher response questionnaires for practicality, and pre-test and post-test sheets for effectiveness. The results showed that the e-module was valid with a score of 4.00, indicating it was appropriate for use. The practicality, based on student response questionnaires, was 75.34%, and for teachers, it was 75.45%. Effectiveness was tested using a t-test with a significance value of 0.00 and an N-Gain score of 0.31, categorized as moderate.